Improving quality of electronic health records with SNOMED - Duarte, Júlio (2014)
The use of classifications, standards and terminology proves to be of particular importance to classify therapist techniques, clinical and nursing procedures and formulate diagnoses. This work shows a different implementation than usual, the application developed doesn’t depend of platform of medical record. The Department of pathological anatomy was chosen as a pilot service to enter the SNOMED system, to produce reports and to evaluate the benefits of its use in a real context. The successful implementation is directly related to the success of interoperability between information and the use of electronic health record systems. It is the first step to extend the system to the whole hospital and to the success of clinical research, to provide alerts and prevention systems and reduce medical errors.